A Case of Pain, Factitious Disorder and Boundary Violations. (1st December 2001) - Cote, Isabelle
Abstract : Although health professionals are usually familiar with factitious disorders, evaluating such cases may be complicated, particularly in the legal arena. This article describes a patient who presented with pain complaints to numerous doctors. Eventually, a malpractice suit was brought against one of the patient's physicians who had diagnosed her condition as multiple personality disorder (dissociative identity disorder). Factitious disorder and the doctor's prescription of pain medications were issues raised during the trial. In view of the issue of harm, physicians' responsibilities and limitations during ongoing medical care are addressed in this case report.